Risk Factors of Positive Endocervical Curettage and Predictive Model Construction Based on Primary Human Papillomavirus Screening - Hangjing Gao MS; Guanxiang Huang MS; Binhua Dong MS; Ye Li MS; Hongning Cai MD; Xianqian Chen MS; Tingting Jiang MS; Kelvin Stefan Osafo MS; Dabin Liu MS; Jiancui Chen MS; Huihua Ge MS; Diling Pan MS; et al. (Technology in Cancer Research & Treatment)
Introduction The utility and application of endocervical curettage (ECC) during colposcopy remain controversial. This study optimized ECC application for primary human papillomavirus (HPV) screening in patients with high-risk (HR)-HPV. Methods This retrospective study included patients with HR-HPV, who underwent subsequent cervical biopsy and ECC from January 1, 2014, to December 31, 2020. Logistic regression was used to calculate the odds ratios (ORs) and 95% confidence intervals (CIs). The prediction model was presented as a nomogram and evaluated for discrimination and calibration. Results The additional detection rate of cervical intraepithelial neoplasia 2 + lesions with ECC was 2.0% (77/3887) in patients with HR-HPV. In multivariate risk factor analysis, HPV 16 infection presented a high risk of positive ECC, followed by HPV 33, HPV 58, and HPV 31. Irrespective of the abnormal cytopathological results, positive ECC was significantly increased (all P  < .001). Females with acetowhite changes on colposcopy, transformation zone (TZ) type II, TZ type III, colposcopic impression of high-grade squamous intraepithelial lesion, or cancer were at a high risk of positive ECC. The final prediction model included significant variables from risk factor analysis, and had excellent calibration and classification capabilities, with an area under the receiver operating curve of 0.902 (95% CI, 0.881-0.922). Additionally, calibration analysis suggested consistency. Conclusion As the additional detection value of ECC is limited. A satisfactory prediction model was designed to optimize ECC application in patients with HR-HPV infection.